MENGKONSTRUKSI DIRECT PRODUCT NEAR RING DAN SMARANDACHE NEAR RING - Rizky Muhammad Bagas; Titi Udjiani SRRM; Harjito Harjito (Diponegoro University, 2019)
If we have two arbitrary non empty sets ,then their cartesian product can be constructed. Cartesian products of two sets can be generalized into number of sets. It has been found that if the algebraic structure of groups and rings are seen as any set, then the phenomenon of cartesian products of sets can be extended to groups and rings. Direct products of groups and rings can be obtained by adding binary operations to the cartesian product. This paper answers the question of whether the direct product phenomenon of groups and rings can also be extended at the near ring and Smarandache near ring ?. The method in this paper is by following the method in groups and rings, namely by seen that near ring and Smarandache near ring as a set and then build their cartesian products. Next, the binary operations is adding to the cartesian products that have been obtained to build the direct product definitions of near ring and near ring Smarandache.